Implementasi Pengelolaan Dana Program BEASISWA TANGERANG CERDAS Tahun 2023 Untuk Meningkatkan Pemerataan Akses dan Mutu Pendidikan di Kota Tangerang - Tri Nurul Aida; Laeli Nur Khanifah; Siti Dina Setiani; Siti Alya Aryanti (Jurnal Media Administrasi, 2025)
This research entitled “Implementation of the Tangerang Smart Scholarship Program Fund Management Year 2023”. The objectives are the effectiveness of fund management and the impact of the of the scholarship program on access and quality of education for students from underprivileged families underprivileged families. The method used is a qualitative approach with data collection through interviews, observation, and literature study. Participants.Participants included the Education Office, Social Affairs Office, schools, and parents of students, who provided in-depth insights into the program management and policies. who provided in-depth insights into program management and education policy. The results showed that the Tangerang Smart Scholarship Program Scholarship Program has had a positive impact in reducing school dropout rates and increasing access to education at the primary and secondary school levels. access to education at the primary and junior secondary school levels. This program program helps students from low-income families to continue their education without being hindered by financial factors. without being hindered by financial factors, so that they can fulfill their learning needs such as books, uniforms and learning needs such as books, uniforms and transportation. However, there are challenges in managing the funds, especially the delay in distribution that affecting students' educational needs. In addition, the lack of transparency in scholarship recipient data leads to inaccuracies in the determination of scholarship recipients, with some students who did not meet the criteria still receiving the scholarship. scholarships. Communication between the education and social services offices needs to be improved. Research shows that sub-optimal coordination between the two agencies hindered the synchronization of data